Comparison of the Effect of New Spice Freon Extracts Towards Ground Spices and Antioxidants for Improving the Quality of Bulgarian-Type Dry-Cured Sausage - Balev Dessislav Kostadinov; Nenov Neno Stefanov; Dragoev Stefan Georgiev; Vassilev Kiril Petrov; Vlahova-Vangelova Dessislava Borislavova; Baytukenova Sholpan Baydildaevna; Smolnikova Farida Haripovna (Polish Journal of Food and Nutrition Sciences)
Ground spices are a source of hazards for dry-fermented meat products. Since dry-cured sausages are not subjected to heat treatment, there is a high risk of microbial cross-contamination and physical impurities. The aim of this study was to determine effects of the replacement of 3 g/kg of ground black pepper (Piper nigrum L.), and cumin (Cuminum cyminum) with their aliquots of new freon extracts, and compare them with the effect of 0.2 g/kg antioxidant addition (taxifolin extract from Siberian larch (Larix sibirica Ledeb), rosemary (Rosmarinus officinalis L.) extract, and butylated hydroxytoluene) on sensory properties, color stability, proximate composition, free amino nitrogen and pH of Bulgarian-type dry-cured „Sudjuk“ sausages. The replacement of natural ground spices with aliquots of their extracts improved sensory properties and stabilized the color characteristics of the final product during 30 days of storage at 0–4°C. The addition of 0.2 g/kg rosemary extract was as effective as the addition of freon extracts on the overall assessment to the 14th day of the experiment. It was determined that the addition of antioxidants or spice extracts had no significant effect on proximate composition, pH, and free amino nitrogen accumulation of the “Sudjuk”. The addition of 0.2 g/kg, taxifolin or rosemary extracts and butylated hydroxytoluene was not so efficient in improving the sensory properties and color stabilization in comparison to the new freon spice extracts. The examined spice extracts can be successfully used to improve the quality of “Sudjuk” sausages.